2015
DOI: 10.12659/msm.892684
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Socioeconomic Level, and the Prevalence of Masked Hypertension and Asymptomatic Organ Damage

Abstract: BackgroundThis study aimed to determine the prevalence of masked hypertension (MHT) and its association with asymptomatic organ damage (AOD) in a low socioeconomic district of Ankara, Turkey.Material/MethodsWe retrospectively reviewed data obtained from the medical records of 712 patients with no known diagnosis of hypertension who presented to a polyclinic due to symptoms related to elevated blood pressure (BP) and were screened for MHT. Essential hypertension (EHT) existed in 86 patients screened for AOD. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…After adjustment for baseline characteristics, OH was significantly associated with the riser type circadian rhythm (adjusted odds ratio 4.532, 95% CI: 2.579–7.966). The 24‐h ambulatory BP monitoring is a useful non‐invasive technique for evaluating patients with labile hypertension or episodes of hypotension, as it can reflect the patients’ BP fluctuations and circadian rhythms, and thus offers advantages over traditional office BP measurement17, 18. Elevated night‐time BP and non‐dipping profiles have been evaluated in several studies, and it has been shown that elevated night‐time BP, or inverted dippers, is associated with vascular damage, cardiovascular risk and mortality19, 20.…”
Section: Discussionmentioning
confidence: 99%
“…After adjustment for baseline characteristics, OH was significantly associated with the riser type circadian rhythm (adjusted odds ratio 4.532, 95% CI: 2.579–7.966). The 24‐h ambulatory BP monitoring is a useful non‐invasive technique for evaluating patients with labile hypertension or episodes of hypotension, as it can reflect the patients’ BP fluctuations and circadian rhythms, and thus offers advantages over traditional office BP measurement17, 18. Elevated night‐time BP and non‐dipping profiles have been evaluated in several studies, and it has been shown that elevated night‐time BP, or inverted dippers, is associated with vascular damage, cardiovascular risk and mortality19, 20.…”
Section: Discussionmentioning
confidence: 99%
“…Взаимосвязь социально-экономических факторов с МАГ была доказана при обследовании жителей бедной окраины Стамбула. МАГ в этом исследовании была выявлена у 15% из них, а бессимптомное ПОМ встречалось чаще, чем у лиц со стабильной АГ, что указывало на длительный анамнез скрытой "персистирующей" гипертензии и отсутствие самоконтроля АД [21]. Расовая принадлежность обследованных также влияет на распространённость МАГ: у лиц европеоидной расы она ниже, чем у лиц негроидной расы.…”
Section: распространенность маг в различных популяцияхunclassified
“…Доказано, в частности, что хронический психоэмоциональный стресс, в том числе на рабочем месте, является предиктором развития МАГ. Результаты психологического тестирования показывают, что распространённость сердечно-сосудистых заболеваний и неблагоприятный кардиоваскулярный прогноз чаще ассоциирован с типом личности Д ("distressed"), для которого характерны тревожные расстройства, негативная аффективность, депрессия и низкий социально-экономический статус [21]. Среди больных МАГ с напряженной трудовой деятельностью и типом личности Д фиксировали избыточную стресс-реактивность гемодинамики в тесте "математический счет", которая проявлялась увеличением систолического АД >7%, диастолического АД >6%, ЧСС >10%.…”
Section: факторы риска и патофизиологические детерминанты магunclassified
See 1 more Smart Citation
“…Masked hypertension (MHT) was first defined by Pickering in 1992, and its importance is progressively increasing (1). MHT is a condition wherein blood pressure measured according to hypertension guidelines in office is normal, whereas the mean 24-h ambulatory blood pressure measurement or blood pressure measurement out of office is high (2).…”
mentioning
confidence: 99%